Quantitative methods for assessing the severity of anthracnose on yam (Dioscorea alata) - Simons, S.A.; Green, K. (1994)
Two methods (the individual leaf method and whole plant method) for the quantitative assessment of the incidence and severity of anthracnose (Colletotrichum gloeosporioides on yam were developed and evaluated in the field over 3 growing seasons and are proposed for use in epidemiological studies. The percentage leaf/plant area affected by anthracnose and therefore unable to photosynthesize was used to produce disease assessment keys.